2017
DOI: 10.1111/ijfs.13635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing on the functionality of Bambara groundnut (Vigna subterranea) starch–palmitic acid complex

Abstract: Summary Bambara groundnut is an underutilised African leguminous crop. This study investigated the effect of annealing on the complexing ability and functionality of Bambara groundnut starch with palmitic acid. Corn starch was included as the reference. Annealing created cracks and pores on the surface of Bambara groundnut and corn starches, respectively. Bambara groundnut starch had significantly higher amylose content, higher peak and final viscosities than corn starch. The peak viscosities of native Bambara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Research is further exploring novel uses and promising application areas of legumes for industrial application. For instance, several researchers have reported various ways of improving the functionality of legume starch (Joshi et al, 2013;Joshi et al, 2014;Ahmed et al, 2016;Oyeyinka et al, 2017aOyeyinka et al, , 2017bLeite et al, 2017) and protein (Sun and Arntfield, 2011;Ribotta et al, 2012). However, there is limited information on the use of these starches or proteins for new product development and industrial utilization.…”
Section: Processing and Utilizationmentioning
confidence: 99%
“…Research is further exploring novel uses and promising application areas of legumes for industrial application. For instance, several researchers have reported various ways of improving the functionality of legume starch (Joshi et al, 2013;Joshi et al, 2014;Ahmed et al, 2016;Oyeyinka et al, 2017aOyeyinka et al, , 2017bLeite et al, 2017) and protein (Sun and Arntfield, 2011;Ribotta et al, 2012). However, there is limited information on the use of these starches or proteins for new product development and industrial utilization.…”
Section: Processing and Utilizationmentioning
confidence: 99%
“…The ∆ H value of CS ANN ‐OA complex (3.86−4.21 J/g) was slightly higher than that of CS U ‐OA complex (3.70 J/g). The higher ∆ H value suggested that ANN pretreatment could increase the complexing ability between starch and lipid (Oyeyinka et al., ). This may be attributed to the more voids in CS ANN than in CS U , which can promote more formation of starch–lipid complexes (Nakazawa & Wang, ).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, in another study comparing cooking banana and dessert banana, both have claimed to own potential in acting as an emulsifying agent [122]. Recent study stated that pea (Pea sativum) and Bambara groundnut (Vigna subterranea) is an underutilised food crops in Nigeria and currently explored of its potential in terms of starch isolation [123]. Lastly, litchi or is also known by Malaysian as lychee can be obtained in fresh form or canned in glucose syrup.…”
Section: Tapioca/ Cassavamentioning
confidence: 99%
“…Modification of Bambara groundnut (Vigna subterranea), an underutilised starch source from Nigeria using annealing process reported to have caused cracks and pores on starch surface based on image obtained from SEM [254]. In a study of modifying starch using both hydrothermal treatment which are annealing and HMT, results obtained showed false banana (Ensete ventricosum Musaceae) starch could be possibly used as functional ingredients in both food and pharmaceuticals industry [255].…”
Section: Sweet Potatomentioning
confidence: 99%